From Formal Recognition to Substantive Recognition: Citizenship Challenges of Confucianism in Post–New Order Indonesia - Rika Dilawati; Mohamad Dindin Hamam Sidik (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2026)
This study aims to analyze the gap between formal recognition and substantive recognition of Confucianism in post–New Order Indonesia. Although the state has officially re-recognized Confucianism as a recognized religion since the Reformasi era, its adherents continue to face various challenges related to administrative services, social acceptance, and citizenship equality. This study employs a qualitative approach through a literature review of academic publications, legal documents, state regulations, population data, and previous studies on Confucianism, the politics of recognition, religious freedom, and citizenship in Indonesia. Using Charles Taylor’s politics of recognition perspective, this study identifies four major findings. First, the position of Confucianism within Indonesia’s legal system has undergone historical dynamics characterized by recognition, marginalization, and re-recognition. Second, the formal recognition granted by the state has not fully produced substantive recognition in public services and civil administration practices. Third, various forms of social racism and historical stigma against the Chinese-Confucian community persist despite the abolition of discriminatory state policies. Fourth, the Confucian community has developed various resilience strategies through institutional adaptation, education, social participation, and identity negotiation to maintain its presence within Indonesia’s public sphere. This study demonstrates that legal recognition does not always correspond directly to the realization of citizenship equality. Therefore, broader efforts are necessary to strengthen substantive recognition through policy reform, inclusive public services, and greater social acceptance of minority religious groups. As an original contribution, this study offers an interpretation of the Confucian community’s experience as an example of how recognition operates as a gradual, multilayered, and continuously negotiated process within Indonesia’s multicultural society.